Qué ves cuando las ves. Las mafias italianas en los paisajes lingüísticos de la Ciudad de Buenos Aires - Balsas, María Soledad; Capelli, Francesca (Comparative Cultural Studies: European and Latin American Perspectives, 2023)
In this article we question the visual references to the Italian mafias in the linguistic landscapes in the City of Buenos Aires, through a discursive and ethnographic approach. By analyzing the thematic, rhetorical and enunciative features deployed by the textual surfaces that circulate in public and/or virtual spaces, as well as some significant absences, we aim at problematizing the visual common sense that shapes our individual and collective perceptions on mafia. Due to the proliferation of those visualities and their tendency to spectacularization of the phenomenon of mafias, they would result in a «gaslighting» which tends to naturalize a poorly informed (if not openly biased) interpretation, which paradoxically hides more than what it shows.